2008
DOI: 10.1007/s10817-008-9102-9
|View full text |Cite
|
Sign up to set email alerts
|

Data Complexity of Query Answering in Expressive Description Logics via Tableaux

Abstract: The logical foundations of the standard web ontology languages are provided by expressive Description Logics (DLs), such as SHIQ and SHOIQ. In the Semantic Web and other domains, ontologies are increasingly seen also as a mechanism to access and query data repositories. This novel context poses an original combination of challenges that has not been addressed before: (i) sufficient expressive power of the DL to capture common data modelling constructs; (ii) well established and flexible query mechanisms such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 32 publications
0
82
0
4
Order By: Relevance
“…As for issue 1, an effort has been undertaken to understand which language would be best suited for representing ontologies in a setting where an ontology is used for accessing large quantities of data [7,26,17]. This work has shown that most of the languages proposed so far are not really suited for this task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for issue 1, an effort has been undertaken to understand which language would be best suited for representing ontologies in a setting where an ontology is used for accessing large quantities of data [7,26,17]. This work has shown that most of the languages proposed so far are not really suited for this task.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that OWL, the W3C Web Ontology Language for the Semantic Web 5 , if not restricted, is not suited as a formalism for representing ontologies with large amounts of instance assertions in the ABox [7,26,17], since reasoning in such a logic is inherently exponential (coNP-hard) with respect data complexity, i.e., with respect to the size of the ABox.…”
Section: Introductionmentioning
confidence: 99%
“…First, it is trivial to see that in theory query bases always exist. 3 Second, ans is expected to be mostly complete (T usually includes few "problematic" constructors) leaving few queries that need to be evaluated using the fully-fledged OWL 2 DL system. Third, it has been shown [19] that even in cases that Hydrowl needs to use ans , the scalable system can still be exploited in order to speed up the evaluation by ans .…”
Section: Techniques Used In Hydrowlmentioning
confidence: 99%
“…Unfortunately, query answering over OWL 2 DL ontologies is of very high computational complexity [3,4] and even after modern optimisations and intense implementation efforts [5] OWL 2 DL systems are still not able to cope with datasets containing billions of data.…”
Section: Introductionmentioning
confidence: 99%
“…The only known studies related to this topic are the work on CARIN [20], which has shown decidability of nonrecursive positive Datalog with the DL ALCN R, and the studies on conjunctive query answering in DLs (see e.g. [7,24,25,14,15]), which are indirectly related to integrating Datalog and DLs (since conjunctive queries can be seen as nonrecursive Datalog programs consisting of a single rule).…”
Section: Introductionmentioning
confidence: 99%